Intercultural Leadership in the Context of An Empirical Study in Iran and Switzerland - Radosław Ryńca; Yasmin Ziaeian (Communications of International Proceedings, 2020)
This paper presents an analysis of the differences in the leadership style and links the existing theories with practice. This study will show what kind of leadership styles exist and how they specifically affect the company’s performance results. The aim of this paper is examining the leadership style of one company but in different countries, therefore, the answers provided by executive managers are essential, and the sample size is small. Here, the human resource management of a specific large company in two countries is examined. They are different in terms of political and economic aspects. For the needs of comparing the leadership style in one international company based in two different countries (Switzerland and Iran), cultural characteristics need to be determined. For this purpose, Bass & Avolio’s MLQ is administered to executives and employees at Buhler AG in Switzerland and its Iran office to measure the leadership style. The result shows, that the cultural dimensions influence the tendency of managers/employees towards transformational/transactional leadership styles in one company but in different countries. According to this research, It is particularly recommended that the leaders in international companies in different environments take cultural aspects more seriously and become more open and supportive of new mindsets and changes, which – in turn – can increase employees’ satisfaction and performance in the work environment.
Keywords: Leadership Style; Intercultural Leadership; Culture; External Factors